Encyclopedia of Life Sciences 2009
DOI: 10.1002/9780470015902.a0021749
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the p53 and p63/p73 Gene Families

Abstract: The tumour suppressor protein p53 is one of the most studied eukaryote proteins. The finding of its paralogues – p63 and p73 – inspired investigations of the whole family. p73 and p63 appeared to have functions distinct from p53 and to be involved in complex regulation of the latter. Evolutionary studies revealed distant homologues of the family not only in vertebrates but also in protostomes and even in nonmetazoans. The evolutionary history of the p53 family and its relatives is complex, controversial and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In this manuscript we present a specific correlation of evolutionary constraints and tumorigenic mutations of mammalian p53 compared to previous literature (Walker et al, 1999;Pintus et al, 2006;Pintus et al, 2007). We have analyzed a large number of data sets to get a detailed phylogenetic analysis of mammalian p53.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this manuscript we present a specific correlation of evolutionary constraints and tumorigenic mutations of mammalian p53 compared to previous literature (Walker et al, 1999;Pintus et al, 2006;Pintus et al, 2007). We have analyzed a large number of data sets to get a detailed phylogenetic analysis of mammalian p53.…”
Section: Discussionmentioning
confidence: 94%
“…Positive selection has also been reported in p53 evolution (Koonin et al, 2005;Rodin and Rodin, 2005). Studies on p53 and p63/p73 families indicated stepwise positive selection in the evolutionary history (Pintus et al, 2006;Pintus et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…A comparison of the rates of nucleotide or codon and amino acid changes has been employed to examine the evolution of the p63 and p73 genes in vertebrates (Pintus et al 2007). Evidence for positive selection of p63 alleles was detected at the time of divergence of Synapsida and Reptiles.…”
Section: The Origins and Evolutionmentioning
confidence: 99%
“…1) (Nedelcu and Tan 2007;Pintus et al 2007;Fernandes and Atchley 2008). This radiation of p53, p63, and p73 proteins seems to have occurred only in the vertebrate lineage as sequenced non vertebrate chordates such as the cephalochordate Florida lancelet, Brachistoma floridae (Bf ) and the two urochordates, Ciona intestinalis (Cs, sea squirt) and Ciona savignyi (Cs) only contain two p53 superfamily members that don't cluster with the vertebrate proteins.…”
Section: Phylogenetic Relationship Of Invertebrate P53 Family Proteinsmentioning
confidence: 99%
“…1) (Nedelcu and Tan 2007;Pintus et al 2007;Fernandes and Atchley 2008) data on the molecular characterization or function of most of these proteins are lacking. Apart from studies in the commonly used model organisms D. melanogaster and C. elegans, published data on p53-superfamily proteins is limited to the starlet sea anemone Nematostella vectensis and to various molluscs.…”
Section: The Function Of P53 Superfamily Members In Early Animalsmentioning
confidence: 99%